Active Cerebrospinal Fluid Exchange System for Treatment of Pyogenic Ventriculitis. Issue 4 (15th September 2021) - Rezai Jahromi, Behnam; Tanskanen, Päivi; Koski-Pàlken, Anniina; Schwartz, Christoph; Koroknay-Pal, Päivi; Romo, Inka; Niemelä, Mika; Siironen, Jari
ABSTRACT: BACKGROUND: Despite recent advances in antibiotic treatment, pyogenic ventricular brain infections are still associated with adverse clinical outcome in 80% of affected patients and mortality rates approaching 60%. The limitation of antibiotic penetration into the cerebrospinal fluid (CSF) challenges the treatment. Intrathecal treatment remains an option for adjunctive therapy to intravenous (iv) antibiotics when the iv therapy fails to sterilize the CFS. Current treatment options do not allow for changing the CSF composition without adversely affecting intracranial pressure (ICP) and power of hydrogen (pH). OBJECTIVE: To investigate if CSF composition exchange has impact on ventriculitis patients. METHODS: We report 2 cases with pyogenic ventriculitis treated with a new intracranial active fluid exchange system that consists of a dual-lumen catheter to facilitate irrigation and drainage coupled with an intelligent digital pump. RESULTS: This new technique allowed us to change the composition of CSF to an antibiotic-consisted fluid. This resulted in the ability to directly modify the concentration of the targeted antibiotics in the CSF, while simultaneously removing bacterial mass without harming brain tissue and controlling ICP and pH. CONCLUSION: Our reported experience shows that drainage of purulent fluid caused by healthcare-associated ventriculitis or meningitis is now possible without harming brain tissue and ICP while also changing the composition of CSF to an antibiotic-consisted fluid. Actively removing pus and altering CSF in this manner had an impact on infection treatment and antibiotic penetration. Further cases are needed to confirm that our treatment algorithm is correctly tailored to assist clinicians in reliably treating this catastrophic condition.